Stigma in Leprosy Patients in the Community : A Systematic Review - Nadya Ulfa Kesumawardani; Bagus Alfrisa; Muhammad Reza Fahlevi Hanafi; Ria Apriliani Waruwu; Syah Fara Dillasani Sirait (International Journal of Public Health, 2024)
The increasing incidence of leprosy in the community causes individuals with leprosy to experience psychological stress. This pressure can come from the individual's internal perceptions such as feeling insecure, feeling embarrassed, and feeling afraid of being shunned. Apart from that, the psychological pressure experienced by individuals can originate from external factors such as discrimination from society, labeling, and isolation in social life. The method used in preparing this article is the PRISMA method with database searches including Google Scholar, Digital Reference Garba, and Science Direct. There are 15 articles selected based on the criteria, namely published in 2018-2023, can be accessed in full text, articles in Indonesian and English, and are qualitative research using the keywords stigma, leprosy sufferers, and community. The articles analyzed were selected according to criteria with results showing that the stigma experienced by leprosy sufferers in the community consisting of self-stigma and public stigma. These two stigmas cause psychological problems in leprosy sufferers.